Research Establishes the Method of Calculation and Evaluationwater Security Index for TraVinh City, TraVinh Province - The Viet, Can; Thi Thom, Nguyen; Van, Can Thu (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1S, 2018)
Abstract: A multivariate analysis is used to calculate the water security index (WSI) for quantification of water security level for Tra Vinh city, Tra Vinh. Wethen propose solutions to improve the effectiveness of management, exploitation and use of sustainable water resources for TraVinh city.This study has developed a set of criteria and parameters that serve as a basis for calculating the WSI for TraVinh, including 53 parameters belonging to 17 criterias of 5 key aspects. As a result, the level of change in water-related security factors for the period 2012 - 2016, respectively, of the WSI scores for the years was: 56.4 (2012); 58.5 (2013); 56.6 (2014); 50.4 (2015) and 37.9 (2016). Keywords : Water securiry, water security index, set of water security indicator, Tra Vinh city. References: [1] UBND thành phố Trà Vinh, 2016, “Báo cáo kết quả thực hiện nhiệm vụ phát triển KT-XH các năm từ 2012 đến 2016”, www.travinh.org.vn. [2] Nguyễn Văn Sánh & NNK, 2010, “Nghiên cứu tài nguyên nước Trà vinh: hiện trạng khai thác, sử dụng và các giải pháp quản lý sử dụng bền vững”, Tạp chí Khoa học 2010:15b 167-177, Trường Đại học Cần Thơ. [3] United Nations University, 2013, “Water Security and the Global Water Agenda: A UN-Water Analytical Brief”, Ontario: United Nations Institute for Water, Environment and Health. [4] Grey, D and Sadoff, C.D, 2007, “Sink or Swim? Water Security for Growth and Development”,Water Policy9(6): 545–571. [5] World Economic Forum, 2009, “World Economic Forum Water Initiative - Managing Our Future Water Needs for Agriculture, Industry, Human Health and the Environment”, Geneva. [6] The GWP/OECD Task Force, 2015, “Securing water, Sustaining growth”. Sweden. [7] Chaves, H.M.L, 2014, “Assessing water security with appropriate indicators: challenges and recommendations”, EFL-School of Technology, University of Brasilia-UnB, Brazil. [8] Jesse J. Newton, 2013, “Development of a Prototype Water Security Self-Assessment Tool for Rural, Remote, and Otherwise Marginalized Communities”, McMaster University, Hamilton, Ontario, Canada. [9] Dunn, G, 2009, “Canadian approaches to assessing water security: an inventory of indicators: policy report”, Program on Water Governance, University of British Columbia, Vancouver, BC, Canada. [10] Asia Development Bank (ADB), 2013, “Asian Water Development Outlook 2013”, Manila. [11] Asia Development Bank (ADB), 2016, “Asian Water Development Outlook 2016”, Manila.